2019
DOI: 10.3390/met9101064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retained Austenite and Non-Metallic Inclusions on the Mechanical Properties of Resistance Spot Welding Nuggets of Low-Alloy TRIP Steels

Abstract: The combination of high strength and formability of transformation induced plasticity (TRIP) steels is interesting for the automotive industry. However, the poor weldability limits its industrial application. This paper shows the results of six low-alloy TRIP steels with different chemical composition which were studied in order to correlate retained austenite (RA) and non-metallic inclusions (NMI) with their resistance spot welded zones to their joints’ final mechanical properties. RA volume fractions were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…At higher temperature regions, free electrons with higher kinetic energy travel to lower temperature regions until it collides with an imperfection or a phonon in the material. Thus, any imperfection such as retained austenite has a direct impact on thermal conductivity and electrical resistivity that are the dominant parameters for calculation of the temperature profiles [58]. The presented model in this study consistent with experimental result at 80 and 100 rpm rotational speeds.…”
Section: Comparison Of the Theoretical And Experimental Results Of Basupporting
confidence: 87%
See 1 more Smart Citation
“…At higher temperature regions, free electrons with higher kinetic energy travel to lower temperature regions until it collides with an imperfection or a phonon in the material. Thus, any imperfection such as retained austenite has a direct impact on thermal conductivity and electrical resistivity that are the dominant parameters for calculation of the temperature profiles [58]. The presented model in this study consistent with experimental result at 80 and 100 rpm rotational speeds.…”
Section: Comparison Of the Theoretical And Experimental Results Of Basupporting
confidence: 87%
“…It is stated that higher hardness could be associated with the transformation products such as retained austenite and high dislocation density [14]. Cortes et al [58] reported the effect of retained austenite on the thermal/electrical properties of five advanced high-strength TRIP steels. The physical properties of TRIP steels are influenced by the presence and quantity of impure atoms and precipitated phases.…”
Section: Comparison Of the Theoretical And Experimental Results Of Bamentioning
confidence: 99%
“…In recent years, there has been a growing utilization of deformation-assisted joining processes driven by an increasing demand of assembling lightweight components. Deformation-assisted joining processes are classified into three distinct groups according to their operating principles:Based on mechanical, hydraulic, and magnetic loading, such as clinching [1,2], self-pierce riveting [3], sheet-bulk compression [4], hydraulic forming [5], and electro-magnetic forming [6];Based on solid-state welding, such as friction stir welding [7], friction spot welding [8] and explosive welding [9];Based on fusion welding combined with plastic deformation, such as resistance spot and projection welding [10] and weldbonding [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on fusion welding combined with plastic deformation, such as resistance spot and projection welding [10] and weldbonding [11].…”
Section: Introductionmentioning
confidence: 99%